Red grape (Vitis vinifera L.) flavonoids down‐regulate collagen type III expression after UV‐A in primary human dermal blood endothelial cells. Issue 9 (28th June 2018) - Di Francesco, Serena; Savio, Monica; Bloise, Nora; Borroni, Giovanni; Stivala, Lucia Anna; Borroni, Riccardo G.
Abstract: Red grape ( Vitis vinifera L .) flavonoids including flavan‐3‐ols (eg, catechin and epicatechin), flavonols (eg, quercetin) and anthocyanins (eg, malvidin) exert anti‐inflammatory and antioxidant activities. In the skin they also have a photoprotective action, and their effects have been extensively investigated in keratinocytes, melanocytes and fibroblasts. Despite their known effects also on blood vasculature, little is known on their activities on human dermal blood endothelial cells (HDBECs), which are critically involved in skin homeostasis as well as in the pathogenesis of neoplastic and inflammatory skin diseases. We sought to study the biological effects of selected red grape flavonoids in preventing the consequences of ultraviolet (UV)‐A irradiation in vitro. Our results show that red grape flavonoids prevent UV‐A‐induced sICAM‐1 release in HDBECs, suggesting that this cell type could represent an additional target of the anti‐inflammatory activity of flavonoids. In addition, flavonoids effectively inhibited UV‐A‐induced synthesis of collagen type III at both RNA and protein level, indicating that dermal blood microvasculature could be actively involved in ECM remodelling as a consequence of skin photo‐ageing, and that this can be prevented by red grape flavonoids.